Ainda estou aqui = I'm still here [videorecording (DVD)] - Hauser, Murilo; Lorega, Heitor; Torres, Fernanda, 1965-; Mello, Selton, 1972-; Herszage, Valentina; Kosovski, Luiza; Manoella, Maria, 1978-; Estiano, Marjorie, 1982-; Bárbara, Luz; Mora, Cora; Cunha, Gabriela Carneiro da; Torres, Olívia; et al. (Sony Pictures Home Entertainment, 2025)
While Brazil faces the tightening grip of a military dictatorship, Eunice Paiva, a mother of five, is forced to reinvent herself and her family, resisting the oppression that hangs over the country. From the acclaimed director of Central Station and The Motorcycle Diaries, Walter Salles and based on Marcelo Rubens Paiva's memoir, this story portrays an important part of Brazil's hidden history.